Chemical Reactivity of Supported ZnO Clusters: Undercoordinated Zinc and Oxygen Atoms as Active Sites. Issue 23 (13th November 2020) - Yu, Xiaojuan; Roth, Jannik P.; Wang, Junjun; Sauter, Eric; Nefedov, Alexei; Heißler, Stefan; Pacchioni, Gianfranco; Wang, Yuemin; Wöll, Christof
Abstract: The growth of ZnO clusters supported by ZnO‐bilayers on Ag(111) and the interaction of these oxide nanostructures with water have been studied by a multi‐technique approach combining temperature‐dependent infrared reflection absorption spectroscopy (IRRAS), grazing‐emission X‐ray photoelectron spectroscopy, and density functional theory calculations. Our results reveal that the ZnO bilayers exhibiting graphite‐like structure are chemically inactive for water dissociation, whereas small ZnO clusters formed on top of these well‐defined, yet chemically passive supports show extremely high reactivity ‐ water is dissociated without an apparent activation barrier. Systematic isotopic substitution experiments using H2 16 O/D2 16 O/D2 18 O allow identification of various types of acidic hydroxyl groups. We demonstrate that a reliable characterization of these OH‐species is possible via co‐adsorption of CO, which leads to a red shift of the OD frequency due to the weak interaction via hydrogen bonding. The theoretical results provide atomic‐level insight into the surface structure and chemical activity of the supported ZnO clusters and allow identification of the presence of under‐coordinated Zn and O atoms at the edges and corners of the ZnO clusters as the active sites for H2 O dissociation. Abstract : Chemical nature of small ZnO clusters : The combined infrared reflection absorption spectroscopy (IRRAS) and theoretical results reveal that the Ag(111)‐supported graphitic ZnO bilayers are chemically inactive. Significant activity is observed when small ZnO clusters are supported by these bilayers. This apparently barrier‐free water dissociation takes place at under‐coordinated Zn and O atoms at the edges and corners of the ZnO nanostructures. Various acidic hydroxyl species are identified by isotopic substitution experiments and the formation of weak H bonds to coadsorbed CO molecules.